The construction of identity through art in people at risk of social exclusion - Cara, Cristina Berruezo; Morón Velasco, Mar (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2021)
This article gathers the research that aims to study the impact of art in the construction of the identity of individuals and, specifically, of those who are located in groups at risk of social exclusion. To achieve this objective, an ethnographic investigation is followed through an in-depth semi-structured interview with artists belonging to different groups at risk of social exclusion.After carrying out this research, it has been possible to verify the benefits that art and art education really brings. Benefits that are accentuated in the case of people who are part of a group at risk of social exclusion, since art is a means of expression, self-knowledge, self-determination and empowerment, a mechanism of vindication and, in short, a political and social tool. In addition, it has been seen how the relationship with art gives them recognition and broadens socio-affective bonds through flexibility and understanding of different points of view and association in different groups of belonging. Furthermore, it allows people vulnerable to social exclusion to become part of the society that recognizes their talent and values ​​their work above their personal characteristics. Therefore, it becomes clear the importance of artistic education being part of the Primary Education curriculum as a tool that favors educational and social inclusion
Keywords: art; art education; educational and social inclusion; identity; groups at risk of social exclusioinclusion